Aplikasi ekstrak daun tapak dara (Catharanthus roseus l.) terhadap pertumbuhan dan morfologi tanaman bawang daun (Allium fistulosum l.) - A'yuni Fatkhi Fajriyati; Syaiful Anwar; Florentina Kusmiyati (Jurnal Ilmiah Pertanian, 2022)
Welsh onion (Allium fistulosum L.) is one of the horticultural commodity crops with high consumer value in Indonesia, but production remains low. Efforts to increase the production of Welsh onion can be performed by induction of anti-mitotic substances. Catharanthus roseus leaves contain anti-mitotic alkaloid compounds that promote growth and yield. This research aimed to analyze the effect of extract C. roseus leaf on the growth and morphology of Welsh onion. This research was conducted in Kejajar, Wonosobo, Central Java, followed by analysis in Plant Physiology and Breeding Laboratory, Diponegoro University. This research used a Randomized Block Design (RBD) factorial with three concentrations; 0.05%, 0.1%, and 0.2%, and three levels of soaking duration; 6, 9, and 12 hours. The data were analyzed statistically using ANOVA followed by Post-hoc Test using Honestly Significant Different (HSD) at 5%. The result showed that applying 0.05% C. roseus leaf extract significantly affected sprouting time, number of tillers per plant, number of leaves per plant, fresh weight, and stomatal density. In addition, the interaction between 0.1% C. roseus leaf extract treatment and 12 hours of soaking duration increased root length by 16.67 cm.